Brand identity through a textile perspective: an exploration of the textile expression of Thule - Béen, Johanna (My University, 2023)
The stroller market is characterized by rapid development and innovation, as well as intense competition from several leading brands. Thule Group, which has been the host for this master’s thesis, have during recent years launched their own line of strollers, with the aim to establish themselves on the market. Thule is a brand with an image associated with the outdoors and an active lifestyle. The project examines the brand identity of Thule and its design language, focusing on the textile expression. Using Thule’s stroller model Sleek as a basis for further development, suggestions for a future textile concept have been outlined. These suggestions have been prototyped and applied on the Thule Sleek stroller for concrete visualization. The project has resulted in a few main conclusions, both concerning Thule as a brand and baselines for future development. Suggestions for future developments of Thule’s brand identity includes a focus on their Swedish heritage through a concept based partly on a Scandinavian, minimalistic design language. But it also holds an underlying focus on Thule’s products carrying a range of clever and thought through functions, adding to the usability of the product. One single product design can be developed to suit both outdoor-, and urban fashion standards, considering the main aspects of the different styles in the design process. Thereby minimizing the number of different products needed for a single user. In future design processes the child should be considered a user of the product of equal importance as the adult, considering aspects of comfort, cover, and the need for a “closed space” for periods of rest, as well as other needs identified in the child’s development.
Keywords: Brand Identity, Concept Development, Design Language, Textile Expression, User Experience